Risk factors for superficial vein thrombosis in patients with primary chronic venous disease - Musil, Dalibor; Kaletova, Marketa; Herman, Jiri (VASA, 2016)
BACKGROUND: Primary chronic venous disease (CVD) is associated with an increased risk of superficial vein thrombosis (SVT). While CVD is a predominant factor in SVT, there is a range of additional predisposing factors. The objective was to investigate the association between age, gender, BMI, smoking, oestrogen hormone therapy, family history of venous thromboembolism (VTE) and CEAP clinical classification in patients with CVD and a history of SVT. PATIENTS AND METHODS: In a retrospective observational study on consecutive patients with primary CVD, 641 outpatients were enrolled (152 men, 23.7%; 489 women, 76.3%). The prevalence of SVT was evaluated according to age, BMI, smoking, presence of family history of VTE, use of hormone therapy, and clinical class of CVD. RESULTS: Risk of SVT was significantly increased in women (OR 1.68, 95% CI = 1.02-2.76; p = 0.041), older patients (46-69 years, OR 1.57, 95% CI = 1.03-2.4; p = 0.036, ≥ 70 years, OR 2.93, 95% CI = 1.5-5.76; p = 0.001), smokers (OR 1.69, 95% CI = 1.1-2.58; p = 0.015) and in persons with first-degree siblings diagnosed with VTE (OR 2,28, 95% CI = 1.28-4.05; p = 0.004). The risk was significantly increased in older male smokers (p - 0.042). In women, smoking and oestrogen therapy (p = 0.495) did not increase the risk of SVT even older women or in those with increased BMI. In CVD (C0-C3), a history of episodes of SVT was found in 103/550 (18.7%), in chronic venous insufficiency (CVI) in 27/91 (29.7%). There was a significantly higher prevalence of SVT in patients with CVI (OR 1.70, 95% CI = 1.1-2.5; p = 0.016). CONCLUSIONS: In patients with primary CVD, SVT was significantly associated with female gender. In men, older age, smoking and positive family history of VTE were relevant SVT risk factors. In women, risk factors were older age, BMI ≥ 25 kg/m2 and positive family history of VTE. Compared with C0-C3 clinical classes, CVI significantly increases the risk of SVT.
Keywords: Chi-Square Distribution; Sex Factors; logistické modely; Venous Insufficiency; Humans; index tělesné hmotnosti; lidé středního věku; Body Mass Index; prevalence; Chronic Disease; Female; rizikové faktory; žilní trombóza; dospělí; žilní insuficience; věkové faktory; Venous Thrombosis; lidé; rozdělení chí kvadrát; sexuální faktory; Adult; Pedigree; rodokmen; ženské pohlaví; Male; Middle Aged; Retrospective Studies; chronická nemoc; Genetic Predisposition to Disease; genetická predispozice k nemoci; Czech Republic; Odds Ratio; Prevalence; retrospektivní studie; Age Factors; Risk Assessment; Smoking; Česká republika; mužské pohlaví; odds ratio; kouření; hodnocení rizik; Logistic Models; Risk Factors